Catalytic conversion of methane at low temperatures: a critical review - Chen, Yipei; Mu, Xueliang; Luo, Xiang; Shi, Kaiqi; Yang, Gang; Wu, Tao (Wiley-VCH Verlag, 2019)
The current study reviews the recent development in the direct conversion of methane into syngas, methanol, light olefins, and aromatic compounds. For syngas production, nickel-based catalysts are considered as a good choice. Methane conversion (84%) is achieved with nearly no coke formation when the 7% Ni-1%Au/Al2O3 catalyst is used in the steam reforming of methane (SRM), whereas for dry reforming of methane (DRM), a methane conversion of 17.9% and CO2 conversion of 23.1% are found for 10%Ni/ZrOxMnOx/SiO2 operated at 500oC. The progress of direct conversion of methane to methanol is also summarized with an insight into its selectivity and/or conversion, which shows that in liquid-phase heterogeneous systems, high selectivity (>80%) can be achieved at 50oC, but the conversion is low. The latest development of nonoxidative coupling of methane (NOCM) and oxidative coupling of methane (OCM) for the production of olefins is also reviewed. The Mn2O3–TiO2–Na2WO4/SiO2 catalyst is reported to show the high C2 yield (22%) and a high selectivity toward C2 (62%) during the OCM at 650oC. For NOCM, 98% selectivity of ethane can be achieved when a tantalum hydride catalyst supported on silica is used. In addition, the Mo-based catalysts are the most suitable for the preparation of aromatic compounds from methane.